GAMBARAN PENGETAHUAN IBU HAMIL TENTANG MANFAAT SUNTIK TT (TETANUS TOXOID) DI DESA SABAHOTANG KABPATEN PADANG LAWAS - Lubis, Mutia Sari; Nasution, Nurmaidah; Siregar, Putri Runggu; juliana, Juliana; Harahap, Tina Marito (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
The immunization given to women of childbearing age and pregnant women is the TT immunization which is useful for preventing tetanus. Cases of tetanus are often found in a number of tropical countries and countries that still have low health conditions. This study aims to describe the knowledge of pregnant women about TT immunization. Immunization is giving the body immunity against a disease by putting something into the body so that the body is resistant to diseases that are epidemic or dangerous to someone. Cases of tetanus are often found in a number of tropical countries and countries that still have low health conditions. The method in this research is descriptive. The population in the study were all pregnant women in the village of Sabahotang as many as 42 people. There were 42 samples in this study using a total sampling technique. The results showed that 26 people (61.9%) had insufficient knowledge, 4 people (9.5%) had sufficient knowledge and 12 people (28.6%) had good knowledge. It is hoped that pregnant women and those closest to them are given an understanding of the benefits of getting TT immunization in pregnant women by health workers